Pregnancy Induced Ocular Changes and Associated Risk of Ocular Medications - Kaur, G; Isac, DM; Thomas, S; Koshy, J (Nepal Journal of Obstetrics and Gynaecology, 2015)
Pregnancy is associated with various ocular changes which can be either physiological or pathological or modification in pre existing conditions. These changes are mostly transient, however some can become permanent. Physiological ocular changes include change in ocular adenexa, tear film composition, cornea, refraction and intraocular pressure. Pathological ocular changes occur as a result of pregnancy induced hypertension, pseudotumour cerebri, vascular occlusive disorders and amniotic fluid embolism. Some of the pre-existing ocular conditions worsen during pregnancy which include diabetic retinopathy, grave’s disease, toxoplasmosis, pituitary tumours, meningioma and uveal tumours. Others show improvement in pregnancy such as uveitis, optic neuritis and multiple sclerosis. Yet others are associated with exacerbations during postpartum period as optic neuritis. Knowledge of these changes is important for both ophthalmologists and gynaecologists for proper management of these patients. Also the treatment modalities for various disorders differ between pregnant and non pregnant females. The ophthalmic medications should be used cautiously during pregnancy and lactation to avoid harmful effects in the mother and the fetus. The materials published in Pubmed, Google Scholar webpages and standard books have been used for preparing this paper.